Carboxylic acid derivatives display potential selectivity for human histone deacetylase 6: Structure-based virtual screening, molecular docking and dynamics simulation studies. (August 2018) - Uba, Abdullahi Ibrahim; Yelekçi, Kemal
Graphical abstract: Highlights: Human histone deacetylase 6 (HDAC6) is a well-validated target for anticancer drug design and development. Structure-based virtual screening of ∼72 461 druglike compounds retrieved from Otava database. A total of 4 potential HDAC6-selective inhibitors were identified. Molecular dynamics simulation of their complexes with HDAC6 suggested their stable binding mode over time. Abstract: Human histone deacetylase 6 (HDAC6) has been shown to play a major role in oncogenic cell transformation via deacetylation of α-tubulin, making it a viable target of anticancer drug design and development. The crystal structure of HDAC6 catalytic domain 2 has been recently made available, providing avenues for structure-based drug design campaign. Here, in our continuous effort to identify potentially selective HDAC6 inhibitors, structure-based virtual screening of ∼72 461 compounds was carried out using Autodock Vina. The top 100 compounds with calculated ΔG < −10 kcal/mol were manually inspected for binding mode orientation. Furthermore, the top 20 compounds with reasonable binding modes were evaluated for selectivity by further docking against HDAC6 and HDAC7 using Autodock4. Four compounds with a carboxylic fragment, displayed potential selectivity for HDAC6 over HDAC7, and were found to have good druglike and ADMET properties. Their docking complexes were then submitted to 10 ns-molecular dynamics (MD) simulation using nanoscale MD (NAMD) software, to examine the stability of ligand binding modes. These predicted inhibitors remained bound to HDAC6 in the presence of water and ions, and the root-mean-square deviation (RMSD), radius of gyration (Rg) and nonbond distance (protein-ligand) profiles suggested that they might be stable over time of the simulation. This study may provide scaffolds for further lead optimization towards the design of HDAC6 inhibitors with improved selectivity.